A MODEL OF LECTURER DEVELOPMENT IN AN UNDERDEVELOPED REGION: CASE STUDY UNIVERSITY OF AMAL ILMIAH YAPIS WAMENA - Takdir, Soltan; Ramli, Mansyur; Amang, Baso; Darmawan, Dedy (Journal of Social Politics and Governance (JSPG), 2025)
The primary roles of lecturers are to improve efficiency within the institution and to increase service delivery to students and stakeholders. The purpose of this research is to explore and propose development models, focusing on the power of lecturers, and to analyze the functions that serve as sources of development in higher education. The study employed the qualitative method with a case study aimed at exploring development practices at Amal Ilmiah Yapis Wamena University. Data were collected through semi-structured interviews with key actors at Amal Ilmiah Yapis Wamena University and stakeholder partners from the Jayawijaya District Government. Subsequently, a model was developed based on field findings and refined with input from experts. NVivo application was used to analyze the data. The results indicate that the application of lecturer development at Amal Ilmiah Yapis Wamena University begins with the dimensions of planning, implementation, and evaluation stages of lecturer development. Findings from the case study reveal two additional stages: the diagnostic stageand analyzing the impact of lecturer development. It is expected that the findings will assist institutions and universities in formulating appropriate governance strategies and models to achieve organizational objectives.